1995
DOI: 10.1002/mrm.1910340608
|View full text |Cite
|
Sign up to set email alerts
|

High resolution quantitative relaxation and diffusion mri of three different experimental brain tumors in rat

Abstract: The potential of quantitative parameter images of the relaxation times T1 and T2, the proton density rho and the apparent diffusion coefficient (ADC) to characterize three different experimental rat brain tumors (F98 glioma, RN6 Schwannoma, and E376 neuroblastoma) was studied. All parameter values, as determined in histologically confirmed regions of interest (ROI), were higher in edema than in tumor, which in turn were elevated with respect to normal brain. ROI values of ADC and T2 delivered statistically sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(79 citation statements)
references
References 47 publications
5
73
0
1
Order By: Relevance
“…Majority of the patients were females (83.8%) in our study with a male to female ratio of 1:5 that correspond to that in reported literature (17) . Also, more number of malignant thyroid nodules were found in males (46%) compared to females (18%).…”
Section: Discussionsupporting
confidence: 90%
“…Majority of the patients were females (83.8%) in our study with a male to female ratio of 1:5 that correspond to that in reported literature (17) . Also, more number of malignant thyroid nodules were found in males (46%) compared to females (18%).…”
Section: Discussionsupporting
confidence: 90%
“…1-4) often assuming that reduced ADC reflects increased cellularity. However, while some studies have found a negative correlation between tumor ADC and cellularity (1,3), others have found no such correlation (4,5). The inconsistency most likely arises because ADC is a gross measurement that conflates various physiologic parameters, including cell density, size, shape, permeability, subcellular architecture, and vascular perfusion effects.…”
Section: Introductionmentioning
confidence: 99%
“…DW-MRI derives its image contrast from differences in the motion of water molecules between tissues. In general, cancer tends to have more restricted diffusion than normal tissue, because of the higher cell densities and abundance of intra-and intercellular membranes in cancer [70,71] . These images can be acquired quickly without the administration of exogenous contrast medium.…”
Section: Diffusion-weighted Mrimentioning
confidence: 99%